If you have a quadratic equation in the form
![ax^2 + bx + c = 0](https://tex.z-dn.net/?f=ax%5E2%20%2B%20bx%20%2B%20c%20%3D%200)
you can complete the square with the following instructions.
1. If the coefficient of
![ax^2](https://tex.z-dn.net/?f=ax%5E2)
is not equal to 1, then you will need to divide the whole equation by a. Or simply divide the whole equation by a.
![ax^2 + bx + c = 0 \\ \\ \frac{ax^2}{a} + \frac{bx}{a} + \frac{c}{a} = 0 \\ \\ x^2 + \frac{bx}{a} + \frac{c}{a} = 0](https://tex.z-dn.net/?f=ax%5E2%20%2B%20bx%20%2B%20c%20%3D%200%20%5C%5C%20%5C%5C%20%5Cfrac%7Bax%5E2%7D%7Ba%7D%20%2B%20%5Cfrac%7Bbx%7D%7Ba%7D%20%2B%20%5Cfrac%7Bc%7D%7Ba%7D%20%3D%200%20%5C%5C%20%5C%5C%20x%5E2%20%2B%20%5Cfrac%7Bbx%7D%7Ba%7D%20%2B%20%5Cfrac%7Bc%7D%7Ba%7D%20%3D%200)
2. Then get all the x terms on one side of the equation. We do this by subtracting
![\frac{c}{a}](https://tex.z-dn.net/?f=%5Cfrac%7Bc%7D%7Ba%7D)
from both sides of the equation.
![x^2 + \frac{bx}{a} + \frac{c}{a} - \frac{c}{a} = 0 - \frac{c}{a} \\ \\ x^2 + \frac{bx}{a} = - \frac{c}{a}](https://tex.z-dn.net/?f=x%5E2%20%2B%20%5Cfrac%7Bbx%7D%7Ba%7D%20%2B%20%5Cfrac%7Bc%7D%7Ba%7D%20-%20%5Cfrac%7Bc%7D%7Ba%7D%20%3D%200%20-%20%5Cfrac%7Bc%7D%7Ba%7D%20%5C%5C%20%5C%5C%20x%5E2%20%2B%20%5Cfrac%7Bbx%7D%7Ba%7D%20%3D%20-%20%5Cfrac%7Bc%7D%7Ba%7D)
3. Finally, take the half of the coefficient of
![\frac{bx}{a}](https://tex.z-dn.net/?f=%5Cfrac%7Bbx%7D%7Ba%7D)
, square it and add it to both sides of the equation.
![\frac{bx}{a} = \frac{b}{a}x \\ \\ \frac{b}{2a} \\ \\ (\frac{b}{2a})^2 = \frac{b^2}{4a^2} \\ \\ x^2 + \frac{bx}{a} + \frac{b^2}{4a^2} = \frac{c}{a} + \frac{b^2}{4a^2}](https://tex.z-dn.net/?f=%5Cfrac%7Bbx%7D%7Ba%7D%20%3D%20%5Cfrac%7Bb%7D%7Ba%7Dx%20%5C%5C%20%5C%5C%20%5Cfrac%7Bb%7D%7B2a%7D%20%5C%5C%20%5C%5C%20%28%5Cfrac%7Bb%7D%7B2a%7D%29%5E2%20%3D%20%5Cfrac%7Bb%5E2%7D%7B4a%5E2%7D%20%5C%5C%20%5C%5C%20x%5E2%20%2B%20%5Cfrac%7Bbx%7D%7Ba%7D%20%2B%20%5Cfrac%7Bb%5E2%7D%7B4a%5E2%7D%20%3D%20%5Cfrac%7Bc%7D%7Ba%7D%20%2B%20%5Cfrac%7Bb%5E2%7D%7B4a%5E2%7D)
I hope that helped!